Simulated heat waves affected alpine grassland only in combination with drought. Issue 2 (12th August 2015) - De Boeck, Hans J.; Bassin, Seraina; Verlinden, Maya; Zeiter, Michaela; Hiltbrunner, Erika
Summary: The Alpine region is warming fast, and concurrently, the frequency and intensity of climate extremes are increasing. It is currently unclear whether alpine ecosystems are sensitive or resistant to such extremes. We subjected Swiss alpine grassland communities to heat waves with varying intensity by transplanting monoliths to four different elevations (2440–660 m above sea level) for 17 d. Half of these were regularly irrigated while the other half were deprived of irrigation to additionally induce a drought at each site. Heat waves had no significant impacts on fluorescence ( F v / F m, a stress indicator), senescence and aboveground productivity if irrigation was provided. However, when heat waves coincided with drought, the plants showed clear signs of stress, resulting in vegetation browning and reduced phytomass production. This likely resulted from direct drought effects, but also, as measurements of stomatal conductance and canopy temperatures suggest, from increased high‐temperature stress as water scarcity decreased heat mitigation through transpiration. The immediate responses to heat waves (with or without droughts) recorded in these alpine grasslands were similar to those observed in the more extensively studied grasslands from temperate climates. Responses following climate extremes may differ in alpine environments, however, because the short growing season likely constrains recovery.